IMPLEMENTATION OF ICT BASED PEDIATRIC TELEHEALTH CARE POSYANDU AS AUTOMATIC MONITOR AND IDENTIFICATION OF INFANT’S GROWTH AND DEVELOPMENT - Riries Rulaningtyas; Abidah Alfi Maritsa; Weni Endahing Warni; Soegianto Soelistiono; Khusnul Ain; Amirul Amalia; Aji Sapta Pramulen; Yusrinourdi Muhammad Zuchruf; Hanif Assyarify; Miranda Syafira Widyananda; Muhammad Fadhel Maulama (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Posyandu is one of the Indonesian government’s attempt in order to monitor and improve the health and life quality of the community, especially infant. However, the implementation of Posyandu is facing some issues such as low effectiveness and low accuracy during the data collecting process of the infant’s growth and development. Purpose: This study aims to develop an automatic telehealth care product in order to help to increase the effectivity and accuracy in the implementation of Posyandu. Methods: (1) Development of the Telehealth Care Posyandu Application, (2) Implementation of the application in the form of social service program. Result: (1) “Toddler” Telehealth Care Application based in Android and ICT was buith with artificial intelligence of Decision Tree and Random Forest method. Program testing was done with 97.89% accuration score from total 85 infant’s growth data. While from 47 questionnaire data of infant’s development, accuracy score of 83.33% was obtained. (2) Target’s respond on the Telehealth Care Posyandu Application shown the status of “Very Satistified” based on the score of 81% from the satisfaction survey. The satisfaction survey covered three aspects which are: System, User, and Interaction. Conclusion: “Toddler” Telehealth Care Posyandu Application was proven to has high accuracy, sensitivity, and sensitivity score and also resulted in “Very Satisfied” user respond.